Performance Comparison of Latency for RSC-RSC and RS-RSC Concatenated Codes - Manish Kumar; Jyoti Saxena (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
In this paper, we compare the latency of serially concatenated convolutional codes. In particular, we compare RSC-RSC   concatenated codes using non-iterative concatenated Viterbi decoding to RS-RSC concatenated codes using concatenation of Viterbi & Berklelamp-Massey decoding. We have also used puncturing to obtain different code rates & analyzed the effect of code rate on latency. On the basis of simulations, it is shown that RSC-RSC code is better than RS-RSC codes for low latency applications. It is also shown that a trade-off is needed between BER & latency for concatenated codes.